50 m freestyle in 21, 22 and 23 s: What differentiates the speed curve of world-class and elite male swimmers?. (2nd November 2021) - Barbosa, Augusto C.; Barroso, Renato; Gonjo, Tomohiro; Rossi, Marcel M.; Paolucci, Leopoldo A.; Olstad, Bjørn H.; Andrade, André G. P.
ABSTRACT: We examined the association between 50 m freestyle performance (50FS) and average speed (AS), peak speed (PS), minimum speed (MS) and intracyclic speed variation (ISV) and compared the speed curves from swimmers with different performance levels using functional analysis of variance (FANOVA). Fourteen male swimmers (50FS: 22.50 ± 0.58 s) performed a maximal sprint with a speedometer and AS, PS, MS, and IVV were assessed for correlational analysis. 50FS were obtained in official competitions. Swimmers were assigned to three groups based on actual 50FS: G21 (n = 2, 21.99 ± 0.04 s), G22 (n = 6, 22.82 ± 0.10 s) or G23 (n = 6, 23.55 ± 0.18 s). FANOVA compared the average curves. 50FS correlated to AS ( r = −0.781, p = 0.001) and PS (ρ = −0.766, p = 0.001), but not to MS ( r = −0.185, p = 0.527) or IVV ( r = −0.323, p = 0.259). FANOVA showed that faster swimmers achieved higher PS and stayed longer at the upper part of the curve. 50FS performance is related to average and peak speed assessed with the speedometer. Swimmers should seek techniques to maintain the speed at the upper part of the curve as long as possible.